Prevalence and virulence properties of Vibrio cholerae non-O1, Aeromonas spp. and Plesiomonas shigelloides isolated from Cambe Stream (State of Parana, Brazil) - Gibotti, A.; Saridakis, H. O.; Pelayo, J. S.; Tagliari, K. C.; Falcao, D. P. (Blackwell Science, 2000)
The incidence of Vibrio cholerae, Aeromonas spp, and Plesiomonas shigelloides was determined in Rater samples from Cambe Stream. The samples were collected from seven different sites. The serogroups, virulence markers and drug resistance profiles were also evaluated. Twelve. Aer. hydrophila, 12 Aer. caviae, eight Aer. sobria, seven Ple. shigelloides and two V. cholerae non-O1 were isolated. They belonged to different serogroups and all produced haemolysis in different assays. Five of the Aeromonas strains and one of V, cholerae non-O1 were positive for enterotoxin activity. Haemagglutination and its inhibition, using erythrocytes of different origins, was variable for Aeromonas spp and V. cholerae, while none of the Plt. shigelloides haemagglutinated in association with any type of erythrocyte. All isolates exhibited multiple drug resistance. These results indicate that the occurrence of V. cholerae non-O1, Aeromonas spp, and Ple. shigelloides, in water used for vegetable irrigation, human recreation and animal consumption, among others, represents a potential risk for humans.